Electronic structure of β-NiOOH with hydrogen vacancies and implications for energy conversion applications. (2nd May 2017) - Fidelsky, Vicky; Furman, David; Khodorkovsky, Yuri; Elbaz, Yuval; Zeiri, Yehuda; Caspary Toroker, Maytal
Abstract: Abstract : Nickel oxide-based materials have attracted significant interest for a variety of energy conversion applications although many of their structures remain unresolved. In this study, Density Functional Theory+U (DFT+U) and hybrid DFT calculations are used to analyze the properties of crystalline nickel oxyhydroxide ( β -NiOOH) with hydrogen (H) vacancies. Hydrogen vacancies are found to lower the band gap without creating states inside the band gap. Inter-layer crossing is a possible transport pathway, while intra-layer transport is inhibited. Bulk modulus is not influenced by H vacancies in the crystal. β -NiOOH with H vacancies exhibits good electronic properties, essential for solid electrolytes and anodes in solid oxide fuel cells.